1997
DOI: 10.1101/lm.3.6.545
|View full text |Cite
|
Sign up to set email alerts
|

Reversible inactivation of the cerebellar interpositus nucleus completely prevents acquisition of the classically conditioned eye-blink response.

Abstract: Numerous studies from several laboratories report that temporary inactivation of the cerebellar interpositus nucleus and regions of overlying cortex during eye-blink conditioning completely prevents acquisition of the conditioned eye-blink response (CR) without affecting the ability to learn the CR in subsequent training without inactivation. Recently, these results have been challenged by the suggestion that learning was not completely blocked in these studies. Instead, it has been suggested that low levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 41 publications
9
88
2
Order By: Relevance
“…Accumulated evidence has indicated that both Purkinje cells and interpositus nucleus circuits play a critical role in the execution and proper timing of CRs in associative eyeblink motor learning (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The CS and US signals are conveyed to both the Purkinje cell and the interpositus nucleus circuits, and the convergent information of these two signals is capable of inducing neural plasticity at both circuits (2,26,36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence has indicated that both Purkinje cells and interpositus nucleus circuits play a critical role in the execution and proper timing of CRs in associative eyeblink motor learning (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The CS and US signals are conveyed to both the Purkinje cell and the interpositus nucleus circuits, and the convergent information of these two signals is capable of inducing neural plasticity at both circuits (2,26,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…1a). The localization and underlying mechanisms of eyeblink conditioning have been extensively studied by different approaches including gene targeting (6)(7)(8)(9)(10)(11), lesioning (12)(13)(14)(15), mutant analysis (16), and pharmacological inactivation analyses (17)(18)(19)(20)(21)(22)(23). On the basis of these studies, one model proposes an essential role of the cerebellar Purkinje cell circuit in memory traces (24)(25)(26).…”
mentioning
confidence: 99%
“…The context exposure (CE) group was necessary to control for the effects of exposure to the apparatus in the muscimol group, which could influence performance during phase 2 and affect the ability to detect savings or the absence of savings. Context exposure during muscimol inactivation could facilitate conditioning in phase 2, producing what appears to be savings (Hardiman et al, 1996;Krupa and Thompson, 1997). Although unlikely, context exposure could also impair conditioning in phase 2.…”
Section: Experiments 1: Effects Of Muscimol Inactivation Of the Ipsilamentioning
confidence: 99%
“…The most convincing evidence supporting the idea of memory storage in the cerebellum comes from studies that used reversible inactivation of the cerebellum and efferent premotor nuclei. Inactivation of the cerebellar nuclei that are ipsilateral to the trained eye with muscimol blocks acquisition of eyeblink conditioning in rabbits (Krupa et al, 1993;Hardiman et al, 1996;Krupa and Thompson, 1997). Muscimol inactivation of the cerebellum also prevents savings, indicating that no learning occurred during inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete lesions of the cerebellar interpositus nucleus (electrolytically, chemically, reversibly) consistently and completely prevent the acquisition and permanently and completely abolished retention͞expression of classically conditioned eyeblink responses in rabbits, rats, and mice (20)(21)(22)(23)(24)(25)(26)(27)(28). Cortical lesions affect various aspects of learning including learning rate, asymptotic learning level, learningdependent response timing, and immediate retention, but do not completely and permanently abolish learning (refs.…”
mentioning
confidence: 99%